2019
DOI: 10.1007/s12250-019-00104-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus-1 Replication by Natural Compound Honokiol

Abstract: Honokiol is a pleiotropic natural compound isolated from Magnolia and has multiple biological and clinically relevant effects, including anticancer and antimicrobial function. However, the antiviral activity of honokiol has not yet been well studied. Here we showed that honokiol had no effect on herpes simplex virus-1 (HSV-1) entry, but inhibited HSV-1 viral DNA replication, gene expression and the production of new progeny viruses. The combination of honokiol and clinical drug acyclovir augmented inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Of all Akt drugs tested here, honokiol is the strongest inhibitor for ZIKV replication. This compound has previously shown antiviral activity against DENV [ 36 ], HCV [ 37 ] and herpes simplex virus type 1 [ 38 ]. The mechanism by which honokiol inhibits viral replication remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Of all Akt drugs tested here, honokiol is the strongest inhibitor for ZIKV replication. This compound has previously shown antiviral activity against DENV [ 36 ], HCV [ 37 ] and herpes simplex virus type 1 [ 38 ]. The mechanism by which honokiol inhibits viral replication remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in concentrations might be related to a multitarget effect of honokiol in the whole organism assay, as has been reported for other viral infections. 23 It has been reported that honokiol blocks phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) signaling in various cell lines and induces autophagy in neuroblastoma cells by activating the PI3K/Akt/mammalian target of rapamycin (mTOR) and endoplasmic reticular stress/extracellular signal-regulated kinase (ERK)1/2 signaling pathways. 26 Since honokiol has been used as an Akt inhibitor, the suppressive effect of viral infection might be attributed to properties other than the inhibition of furin-like activities.…”
Section: Resultsmentioning
confidence: 99%
“… 17 , 18 , 19 , 20 Honokiol and magnolol have also been reported to have not only anti-inflammatory, anxiolytic, antidepressant, antioxidant, and anticancer effects, but also antivirus effects (supplemental table). 16 , 21 , 22 , 23 In this study, we explored honokiol as a potential inhibitor of furin, an enzyme involved in the viral entry to the cell. We further tested if honokiol suppressed viral infection in the whole cell assay of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Honokiol also induced apoptosis and reduced the proliferation index in implanted human prostate cancer cell (PC-3) tumors in mice [ 201 ] and had antitumoral effects against angiosarcoma implanted in mice in vivo and as an angiogenesis inhibitor in vitro [ 202 , 203 ]. Its antimicrobial activities include reported antibacterial effects against methicillin-resistant Staphylococcus aureus (MRSA) [ 204 ] and as an antiviral inhibitor of HSV-1 DNA replication and virus production [ 205 ] and HCV entry, replication and protein translation (SI: 5.4) [ 206 ].…”
Section: Honokiolmentioning
confidence: 99%